Planning and Conducting Magnetic Field Level Measurement from Overhead Transmission Line - H.M. Luqman; M.N.R. Baharom; H. Ahmad; Irshad Ullah (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Human population and power consumption keeps on growing with each year. In order to satisfy electricity demand, more electrical energy has to be supplied, resulting in higher magnetic field level radiation. In rapid urbanization country, lack of space will force civilization to be built near overhead transmission line that sparks public concern on adverse health effects due to the magnetic field radiation. A new UTHM hostel residential area was built near OTLs that shared the same concern. Thus a proper planning to conduct magnetic field level measurement was done to examine the maximum magnetic field level radiated that covered the hostel residential area. The results were far from reaching the maximum permissible magnetic field level proposed by ICNIRP. Though, the steps taken and the methods used might be suitable guidelines for others that encounter similar situations.